Handbook of brewing - Stewart, Graham G., 1942-; Anstruther, Anne; Russell, Inge, 1947- (CRC Press, 2018)
"As with two previous editions, the Handbook of Brewing, Third Edition, provides the essential information for those who are involved or interested in the brewing industry. New chapters cover product integrity, sensory evaluation, craft and microbrewing, and environmental and waste disposal issues."--Provided by publisher
Keywords: Brewing -- Handbooks, manuals, etc.; Beer -- History.; elektronické knihy; electronic books